Knowledge, attitude, practice and awareness on hypertension among students and staffs in Faculty of Medicine and Health Sciences (FMHS), Universiti Putra Malaysia - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Jamari, Muhammad Syakirin; Sharif, Nur Fatihah; Paramesvaran, Reshma (University of Malta, 2023)
Introduction: The number of patients diagnosed with hypertension among the population is rising rapidly. Its inherent risk of mortality is a grave cause of concern. Therefore, this study aims to determine the level of knowledge, attitude, practices and awareness on hypertension and associated factors among students and staff in the FMHS, Universiti Putra Malaysia. Methods: A cross sectional study was done at the FMHS, Universiti Putra Malaysia for 17 weeks duration in 2020. Through stratified random sampling, students and staff selected from the faculty answered a questionnaire distributed in Google Documents form via Whatsapp. The data was analyzed using the SPSS v25. Results: 340 students and 87 staff participated in our study. Overall, majority of the students and staffs demonstrated a good level of knowledge, attitude, practice and awareness of hypertension. In multivariate analysis, ethnicity shows a significant association with awareness among students. There was significant association between age with the level of practice of hypertension among staff, and between the field of staff with the level of practice and awareness of hypertension among the staff in multivariate analysis. Conclusion: Majority of the students and staffs demonstrated a good level of knowledge, attitude, practices and awareness among both staffs and students. This augurs well for this current and future health professionals in their battle in reducing the prevalence of hypertension.